Ferritin – The key model inflammatory marker in diabetic and non-diabetic COVID-19 - Kumar, Mukesh; Bindu, CM; Shyam, AC; Reena, R (Asian Journal of Medical Sciences, 2021)
Background: Diabetics exhibit elevated serum ferritin level when compared to non-diabetic counterpart, indicates impact of its association with coronavirus disease 2019 (COVID-19) infection and disease progression. Ferritin is a key mediator of immune dysregulation through direct immunosuppression contributing to cytokine storm resulting in fatal outcome in COVID-19. Aims and Objectives: This study aims to estimate serum ferritin in diabetic (cases) and non-diabetic (controls) COVID-19 patients and its correlation with their diabetic profile (FBS, PPBS, RBS, and HbA1C). Materials and Methods: A retrospective case–control study conducted at Rajarajeswari Medical College and Hospital, Bengaluru, for a period of 8 months among diabetic and non-diabetic COVID-19 patients. Results: The study population consisted of 957 individuals, out of them, 425 patients were type 2 diabetes mellitus and 532 were non-diabetic COVID-19-positive patients (controls). Diabetic profile parameters (FBS, PPBS, RBS, and HbA1c) and serum ferritin were significantly (P<0.05) high in cases as compared to controls. Among diabetic COVID-19, the glycated hemoglobin and serum ferritin showed a significantly positive correlation (r=0.55) with serum ferritin (mean=648.98±320.48). Conclusion: Hyperferritinemia is more prevalent in diabetic COVID-19 individuals. Serum ferritin can be considered as a valuable biomarker to screen the diabetic and non-diabetic for the presence of hyperinflammation and to predict severity of COVID-19 infection so that it will help the clinician for proper management.